2017
DOI: 10.1103/physreve.95.060601
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-long-range dynamic correlations in a microscopic model for aging gels

Abstract: We use large-scale computer simulations to explore the nonequilibrium aging dynamics in a microscopic model for colloidal gels. We find that gelation resulting from a kinetically-arrested phase separation is accompanied by 'anomalous' particle dynamics revealed by superdiffusive particle motion and compressed exponential relaxation of time correlation functions. Spatio-temporal analysis of the dynamics reveals intermittent heterogeneities producing spatial correlations over extremely large length scales. Our s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Another way to capture dynamic heterogeneities [42] is the calculation of the mobility map, which allows us to visualize the single-particle dynamics over a given length-scale. To connect particle deformations to the dynamical heterogeneities occurring at high ζ we thus calculate the mobility function s i (∆t) = 1 − exp[δr 2 i (∆t)/2a 2 ] for all rings, where a is a length scale which can be tuned to probe different regimes and ∆t is the time interval between two configurations from which particle displacement δr 2 i is evaluated.…”
Section: F Mobility Maps Of Eprsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to capture dynamic heterogeneities [42] is the calculation of the mobility map, which allows us to visualize the single-particle dynamics over a given length-scale. To connect particle deformations to the dynamical heterogeneities occurring at high ζ we thus calculate the mobility function s i (∆t) = 1 − exp[δr 2 i (∆t)/2a 2 ] for all rings, where a is a length scale which can be tuned to probe different regimes and ∆t is the time interval between two configurations from which particle displacement δr 2 i is evaluated.…”
Section: F Mobility Maps Of Eprsmentioning
confidence: 99%
“…The fraction of these islands varies with softness and packing fraction, thereby resulting in state-point-dependent exponents for the compressed exponential relaxation and for the super-diffusive behavior.The compressed exponential relaxation is still an important open question in colloidal systems and glass-formers [33,40,41]. Simulations recently provided some clues in this process by looking into phase-separating systems [42] and by artificially altering the network dynamics [43]. Alternatively a coarse-grained elasto-plastic model has been discussed to go beyond mean-field predictions on stress-driven dynamics [44].…”
mentioning
confidence: 99%
“…From (Ruta et al, 2013). in supercooled liquids (Caronna et al, 2008), colloidal suspensions (Angelini et al, 2013) and even in hard amorphous materials like metallic glasses (Ruta et al, 2013(Ruta et al, , 2012. Although this anomalous relaxation was observed ubiquitously in experimental systems, it took more than a decade to reproduce dynamics with compressed exponential decay in molecular-scale simulations, until Bouzid et al (2017) and Chaudhuri and Berthier (2017) eventually reported such dynamics in microscopic models for gels. The main obstacle had been to probe the right parameter range, notably with respect to temperature and also length scales.…”
Section: A Relaxation and Agingmentioning
confidence: 99%
“…26,27 In fact, theoretical and simulation studies suggest that long-range anisotropic stresses arising from dipole forces are integral to understanding aging in disordered matter. 28,29 Even in the deeply supercooled liquid state, there are indications that the relaxation dynamics can be described through an accumulation of Eshelby transformations; i.e., local structural rearrangements resulting in long-range stress fluctuations and elastic strains 30,31 . In this sense, the compressed form of the exponential relaxation function of metallic glasses probed in XPCS might also result from a series of such Eshelby transformations, each contributing a Debye term with a well-defined relaxation time.…”
Section: Resultsmentioning
confidence: 99%